Empowering Community Through Sacred Rituals: A Participatory Action Study on Funeral Management in Islamic Traditions - Hendi Sugianto; Sahjad M. Aksan; Siti Muti’ah; Turmuji Jafar; Iklal Jamaluddin (Communautaire: Journal of Community Service, 2024)
This research focuses on increasing knowledge, skills, and community participation in the management of bodies in accordance with Islamic sharia through training and mentoring at the Taklim Council. The main objective of this study is to explore the effectiveness of community-based training in building individual competencies and strengthening social solidarity within the Muslim community. This study uses a qualitative method with a Participatory Action Research (PAR) approach, which involves the active participation of community members at the Thariqul Falah Taklim Council, Toboleu Village, Ternate City. The data were collected through participatory observation, in-depth interviews, and focused group discussions, then analyzed using Miles and Huberman's interactive analysis technique consisting of three stages: data reduction, data presentation, and conclusion drawn/verification. The results of the study showed that the training succeeded in improving the participants' theoretical knowledge, practical skills, and confidence in caring for the body, as well as strengthening the sense of collective responsibility and community solidarity. The implications of this study emphasize the importance of a participatory approach and flexibility in the implementation of community-based training to ensure the sustainability and effectiveness of future religious education programs.